2022
DOI: 10.3390/biomedicines10112770
|View full text |Cite
|
Sign up to set email alerts
|

Are Antisense Long Non-Coding RNA Related to COVID-19?

Abstract: Fighting external pathogens relies on the tight regulation of the gene expression of the immune system. Ferroptosis, which is a distinct form of programmed cell death driven by iron, is involved in the enhancement of follicular helper T cell function during infection. The regulation of RNA is a key step in final gene expression. The present study aimed to identify the expression level of antisense lncRNAs (A2M-AS1, DBH-AS1, FLVCR1-DT, and NCBP2AS2-1) and FLVCR1 in COVID-19 patients and its relation to the seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…A2M-AS1 probably has an anti-proliferation and pro-apoptosis effect [37], and LEF1-AS1 and RORA-AS-1 have been found to be involved in T cell differentiation in COVID-19 patients [38]. The decreased levels of A2M-AS-1 in severe COVID-19 patients are in accordance with a previous study [39].…”
Section: Discussionsupporting
confidence: 90%
“…A2M-AS1 probably has an anti-proliferation and pro-apoptosis effect [37], and LEF1-AS1 and RORA-AS-1 have been found to be involved in T cell differentiation in COVID-19 patients [38]. The decreased levels of A2M-AS-1 in severe COVID-19 patients are in accordance with a previous study [39].…”
Section: Discussionsupporting
confidence: 90%
“…In Dr. Hong's studies in 2022, it was shown that this LncRNA is a positive regulatory factor with an increased expression pattern to promote breast cancer metastasis (17). Through the interaction with PCBP3(18), increasing the expression in the diagnosis of progression and prognosis of breast cancer (19), decreasing the expression level of A2M-AS1 in the lung tissue of patients with COVID-19 severe compared to control subjects (20). In the studies of Dr. Guo in 2022, it was shown that the overexpression of A2M-AS1 through the regulation of miR-587/bmp3 inhibits cell growth and invasion in lung adenocarcinoma (19).…”
Section: Discussionmentioning
confidence: 99%
“…Zhong et al showed that the lncRNAs expression profile may identify between severe and non-severe COVID-19 cases, as well as between healthy people and infected patients (Zhong et al, 2022). Measurement of expression of the lncRNAs levels may help predict and monitor patient treatment, according to research by Badr et al that found A2M-AS1 and NCBP2AS1-1 to be useful in differentiating between severe and moderate SARS-CoV-2 infections (Badr et al, 2022). Cheng et al developed a 7-lncRNA panel with a good differential ability between severe and non-severe COVID-19 patients.…”
Section: Ncrnas As Diagnostic Biomarkersmentioning
confidence: 99%